Impact of polysialylated CD56 on natural killer cell cytotoxicity - Kaltschmidt Christian; Schmitz Juergen; Widera Darius; Moebius Jeannette M; Piechaczek Christoph (BMC Immunology, 2007)
Abstract Background Siglec-7, a sialic acid binding inhibitory receptor expressed by NK cells is masked in vivo by a so far unknown ligand. It shows a strong binding prevalence for α-2,8-linked disialic acids in vitro. Results Here we describe the expression of PSA-NCAM (α-2,8-linked polysialic acid modified NCAM) on functional adult peripheral blood natural killer cells and examine its possible role in masking Siglec-7. Unmasking of Siglec-7 using Clostridium perfringens neuraminidase massively reduces NK cell cytotoxicity. By contrast a specific removal of PSA using Endo-NF does not lead to a reduction of NK cell cytotoxicity. Conclusion The results presented here therefore indicate that PSA-NCAM is not involved in masking Siglec-7.